Modular Assembly of Host–Guest Metal–Phenolic Networks Using Macrocyclic Building Blocks. (13th November 2019) - Pan, Shuaijun; Guo, Rui; Bertleff‐Zieschang, Nadja; Li, Shanshan; Besford, Quinn A.; Zhong, Qi‐Zhi; Yun, Gyeongwon; Zhang, Yunti; Cavalieri, Francesca; Ju, Yi; Goudeli, Eirini; Richardson, Joseph J.; et al.
Abstract: The manipulation of interfacial properties has broad implications for the development of high‐performance coatings. Metal–phenolic networks (MPNs) are an emerging class of responsive, adherent materials. Herein, host–guest chemistry is integrated with MPNs to modulate their surface chemistry and interfacial properties. Macrocyclic cyclodextrins (host) are conjugated to catechol or galloyl groups and subsequently used as components for the assembly of functional MPNs. The assembled cyclodextrin‐based MPNs are highly permeable (even to high molecular weight polymers: 250–500 kDa), yet they specifically and noncovalently interact with various functional guests (including small molecules, polymers, and carbon nanomaterials), allowing for modular and reversible control over interfacial properties. Specifically, by using either hydrophobic or hydrophilic guest molecules, the wettability of the MPNs can be readily tuned between superrepellency (>150°) and superwetting (ca. 0°). Abstract : Gut vernetzt : Die Synthese phenolischer Wirtbausteine aus makrocyclischen Wirtringen und koordinierenden Phenolfunktionen ermöglicht den raschen Aufbau adhärierender konformer Metall‐Phenolnetzwerk‐Beschichtungen auf unterschiedlichen Substraten mit modularen und einstellbaren Grenzflächeneigenschaften mithilfe von Wirt‐Gast‐Chemie.